2022
DOI: 10.1111/sum.12849
|View full text |Cite
|
Sign up to set email alerts
|

Aging of colloidal contaminants and pathogens in the soil environment: Implications for nanoplastic and COVID‐19 risk mitigation

Abstract: Colloidal contaminants and pathogens are widely distributed in soil, whose tiny sizes and distinct surface properties render unique environmental behaviours.Because of aging, colloids can undergo dramatic changes in their physicochemical properties once in the soil environment, thus leading to diverse or even unpredictable environmental behaviour and fate. Herein, we provide a state-of-art review of colloid aging mechanisms and characteristics and implications for risk mitigation. First, we review aging-induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 196 publications
0
3
0
Order By: Relevance
“…The temporal changes in metal(loid) immobilization performances add complexity when assessing the long‐term effectiveness of immobilization (Hou et al., 2021; Wang, Hu, et al., 2023; Zhao et al., 2020). On the one hand, we observed that the amended soil underwent a decline in pH over time, which promoted the immobilization of As and Sb but was not favourable for the long‐term immobilization of Cd.…”
Section: Resultsmentioning
confidence: 99%
“…The temporal changes in metal(loid) immobilization performances add complexity when assessing the long‐term effectiveness of immobilization (Hou et al., 2021; Wang, Hu, et al., 2023; Zhao et al., 2020). On the one hand, we observed that the amended soil underwent a decline in pH over time, which promoted the immobilization of As and Sb but was not favourable for the long‐term immobilization of Cd.…”
Section: Resultsmentioning
confidence: 99%
“…Both positive and negative priming could occur for biochar amended soils. The former one refers to the process where carbon mineralization is stimulated, while the latter one refers to the process where the mineralization rate is lowered (thus leading to suppressed CO 2 emissions) (Maestrini et al 2015;Wang et al 2022c). Positive priming is induced via the addition of fresh labile carbon which can stimulate the activities of soil microorganisms, thus accelerating the carbon mineralization process (Fang et al 2019;Keith et al 2011;Zimmerman and Ouyang 2019).…”
Section: Co 2 Emissionsmentioning
confidence: 99%
“…Weathering of plastics is a major process responsible for the breakdown of larger plastics into micro‐ and nanoplastics (Duan et al, 2021). As‐formed MPs break into even smaller particles with progressive weathering, generating nanoplastics (NPs) whose size fall within the nanometre range (Lau et al, 2020; Wang, Hu, et al, 2022). There is some controversy about the definition of nanoplastics (NPs) (Wang, Wu, et al, 2021).…”
Section: Introductionmentioning
confidence: 99%